PERAN DAN UPAYA PENGEMBANGAN LITERASI INFORMASI PERPUSTAKAAN SEKOLAH PADA ERA DISRUPSI1 - I Nyoman yasa (ACARYA PUSTAKA, 2018)
PERAN DAN UPAYA PENGEMBANGAN LITERASI INFORMASIPERPUSTAKAAN SEKOLAH PADA ERA DISRUPSI1OlehDr. I Nyoman Yasa, S.Pd., M.A.Email: inyomanyasa.sastraundiksha@gmail.comABSTRACTThe still existing traditional libraries should develop in keeping with the development of theera. The era development: digital disruption, however, has created ( given birth to) itsgeneration: Gen-Y (Millennial) and Gen-Z. These generations cannot be forced to follow theold pattern, since they were indeed born from the modern/postmodern generation: internet;social media. To improve information literacy of this generation, school libraries have a rolethat is not the same as in the previous era. Librarians/ schools who manage the schoollibraries should provide a broader and easy access facilities. This is very urgent in order thestudents no longer find the libraries in their schools only full with old books. Hence, theschool library plays an innovative role in today’s era.Keywords: role, development, literacy, library, disruptionKeywords: The Role, Library, Information, Literacy ,Disruption